쌀 가공식품 원료의 원산지 선호에 영향을 미치는 요인 - 한재환; Jae-Hwan Han (농업생명과학연구, 2014)
본 연구는 쌀 가공식품 원료에 대한 소비자 선호에 영향을 미치는 요인 분석을 위해 순환이변량프로 빗 모형을 이용하였다. 연구의 목적을 달성하기 위해 인터넷을 이용하여 소비자조사를 수행하였다. 분석결과는 만약 소비자가 쌀 가공식품 구입 시 상대적으로 맛을 더 고려하거나 가격을 가장 중요시할 경우, 쌀의 원산지는 구입의향에 유의한 영향을 주지 않는 것으로 나타났다. 또한 남성이나 기혼자는 여성과 미혼자에 비해 수입쌀로 제조된 쌀 가공식품 소비에 거부감이 낮았다. 반면에 연령이 30~49 그룹의 소비자는 쌀 원산지에 큰 관심을 보였다. 향후 쌀 가공식품 산업을 어둡게 전망하는 소비자의 경우 쌀 가공식품에 사용되는 쌀 원산지가 매우 중요하다고 인식하고 있다. This study investigates various factors affecting consumer preferences for raw material of rice processed foods by employing a recursive bivariate probit model. To accomplish the objective of the study the consumer survey was administered by web mail. The results show that if the main reason consumer purchase the rice processed foods is taste and price is an important criterion to buy them, country of origin of rice is not a significant factor for their purchase intention. It is demonstrated that male and the married have relatively less resistance against foods manufactured with imported rice. In addition, 30~49 age group shows a big concern about country of origin of rice. Consumers who cast a bleak outlook on the rice processed foods market perceive a country of origin as an very important factor.